2005
DOI: 10.2174/1568005054880172
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone-Based Drugs Against Toxoplasma gondii and Plasmodium spp

Abstract: Owing to the rapid emergence of multi-resistant strains of Plasmodium spp. (the causative agents of malaria) and the limitations of drugs used against Toxoplasma gondii (an important opportunistic pathogen associated with AIDS and congenital birth defects), the discovery of new therapeutical targets and the development of new drugs are needed. The presence of the prokaryotic-like organelle in apicomplexan parasites (i.e. plastids), which comprise these major human pathogens, may represent a unique target for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 125 publications
(242 reference statements)
0
8
0
Order By: Relevance
“…1) 25 that are also active against transmissible malaria parasites. Quinolones also display activities against Tg 26 , and here too newer compounds, e.g. ELQ-271 ( Fig.…”
mentioning
confidence: 90%
“…1) 25 that are also active against transmissible malaria parasites. Quinolones also display activities against Tg 26 , and here too newer compounds, e.g. ELQ-271 ( Fig.…”
mentioning
confidence: 90%
“…A plausible explanation of the activity of this class of antibiotics on P. falciparum came from the sequencing of its entire genome, 7,8 and from the recent biochemical characterization of gyrases and topoisomerase IV which could be the main targets of (fluoro)quinolones. 9,10 Using a dual strategy combining a prodrug/ bioorganometallic approach, we recently improved the antimalarial activity of ciprofloxacin (CIPRO 1). 11 This strategy revealed that the prodrug approach resulted in a dramatic increase of the antimalarial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent absence of gyrases in humans and their presence in Plasmodium falciparum make it an excellent target for a range of antibacterial agents. In fact, various quinolone drugs and their deriv-atives that are very potent against bacteria have also been shown to disrupt P. falciparum parasites (2,3,10,15). However, efforts to use gyrase inhibitors to kill the parasites have been somewhat limited due to the nonavailability of recombinant enzymes from Plasmodium falciparum to study biochemical activity and screen inhibitors.…”
mentioning
confidence: 99%